ANALYSIS OF EMPLOYEE PERFORMANCE IMPROVEMENT STRATEGIES AT FURNITURE SHOPS IN PALEMBANG CITY - Susi Handayani; Musa Hubeis; Nancy Yusnita (Yayasan Education and Social Center, 2023)
Factors that influence the performance of employees in Furniture stores is the organizational culture. If the organizational culture in the store does not encourage employees to maintain work discipline, then this can have an impact on the lack of employee compliance with the rules and policies in the store. In addition, work motivation and job satisfaction of employees can also affect their performance. If employees are satisfied with their jobs and get enough motivation, then this can increase their performance and productivity. In this furniture store, workers lack discipline and do not comply with regulations, but the income of furniture stores in Palembang is quite high and stable every month. Field research with a qualitative approach is a type of research that focuses on an in-depth and detailed understanding of the phenomenon being studied. Data collection techniques used in this study were interviews and observation. From the results of the study, it can be concluded that Furniture stores in Palembang have implemented strategies to improve employee performance well by using various aspects such as ability and work expertise, work motivation, leadership, organizational culture, and job satisfaction. However, there are still obstacles to the work discipline aspect where there are still many employees who arrive late, permits for various reasons and have not complied with the regulations are made. Meanwhile, on the career aspect, Furniture stores have not implemented career management for their employees, only increasing salaries gradually as a form of loyalty to the store. Even so, the Furniture store has implemented the compensation aspect well.